Developmental, Morphological and Physiological Traits in Plants Exposed for Five Generations to Chronic Low-Level Ionising Radiation - Caplin, Nicol M.; Halliday, Alison; Willey, Neil J. (Frontiers in Plant Science, 2020)
The effects of ionising radiation (IR) on plants are important for environmental protection but also in agriculture, horticulture, space science, and plant stress biology. Much current understanding of the effects of IR on plants derives from acute high-dose studies but exposure to IR in the environment frequently occurs at chronic low dose rates. Chronic low dose-rate studies have primarily been field based and examined genetic or cytogenetic endpoints. Here we report research that investigated developmental, morphological and physiological effects of IR on Arabidopsis thaliana grown over 7 generations and exposed for 5 generations to chronic low doses of either 137Cs (at a dose rate of c. 40 Gy/h from / emissions) or 10M CdCl2. In some generations there were significant differences between treatments in the timing of key developmental phases and in leaf area or symmetry but there were, on the basis of the chosen endpoints, no long-term effects of the different treatments. Occasional measurements also detected no effects on root growth, seed germination rates or redox poise but in the generation in which it was measured exposure to IR did decrease DNA-methylation significantly. The results are consistent with the suggestion that chronic exposure to c. 40 Gy/h can have some effects on some traits but that this does not affect function across multiple generations at the population level. This is explained by the redundancy and/or degeneracy between biological levels of organisation in plants that produces a relatively loose association between genotype and phenotype. The importance of this explanation to understanding plant responses to stressors such as IR is discussed. We suggest that the data reported here provide increased confidence in the Derived Consideration Reference Levels (DCRLs) recommended by the International Commission for Radiological Protection (ICRP) by providing data from controlled conditions and helping to contextualise effects reported from field studies. The differing sensitivity of plants to IR is not well understood and further investigation of it would likely improve the use of DCRLs for radiological protection.